Visioning workshops in the Tunisian ALL: Preliminary Data Sets of the Visioning Approach - Rudiger, Udo; Ouerghemmi, Hassen; Alary, Veronique; Idoudi, Zied; Frija, Aymen; Rekik, Mourad; Souissi, Asma; Dhehibi, Boubaker; M'hamed, Hatem Cheikh; Triomphe, Bernard (International Center for Agricultural Research in the Dry Areas, 2022)
Within the “Transdisciplinary co-creation of innovations in Agroecological Living Landscape-ALL” Work Package (WP) of the Transformational Agroecology Across Food, Land and Water Systems Initiative (AE-I) , it is proposed to use/apply participatory methods to build collectively a vision of the desired agroecological pathways in each ALL. This activity aims at developing the most suitable agroecological transition pathways in each ALL identified and agreed upon among actors. The Visioning activity was collectively conducted by ICARDA, and its national partners involved in the AE-I under the supervision with all the WP leaders in Tunisian and the support of the “Transdisciplinary co-creation of innovations in Agroecological Living Landscapes” work package WP1 and the “Strengthening the policy- and institutional-enabling environment” work package (WP5) leaders and co-leaders in the first phase of the implementation. This technical report restitutes the primary data collected during the Visioning approach that will support further analysis in the coming months to support the next steps of codesigning and co implementing the technical and organizational agro-ecological innovative packages with the stakeholders in the Tunisian ALL.